Molecular characterisation of Candida auris isolates from immunocompromised patients in a tertiary‐care hospital in Kuwait reveals a novel mutation in FKS1 conferring reduced susceptibility to echinocandins. Issue 3 (3rd January 2022) - Asadzadeh, Mohammad; Mokaddas, Eiman; Ahmad, Suhail; Abdullah, Aneesa A.; de Groot, Theun; Meis, Jacques F.; Shetty, Shama A.
Summary: Background: Candida auris is an emerging, potentially multidrug‐resistant pathogen that exhibits clade‐specific resistance to fluconazole and also develops resistance to echinocandins and amphotericin B easily. This study analysed 49 C auris isolates for alterations in hotspot‐1 and hotspot‐2 of FKS1 for the detection of mutations conferring reduced susceptibility to echinocandins. Methods: C auris isolates ( n  = 49) obtained from 18 immunocompromised patients during June 2016‐December 2018 were analysed. Antifungal susceptibility testing was performed by Etest and broth microdilution‐based MICRONAUT‐AM assay. Mutations in hotspot‐1 and hotspot‐2 regions of FKS1 were detected by PCR sequencing and fingerprinting of the isolates was done by short tandem repeat typing. Results: The patients had multiple comorbidities/risk factors for Candida spp. infection including cancer/leukaemia/lymphoma/myeloma ( n  = 16), arterial/central line ( n  = 17), urinary catheter ( n  = 17), mechanical ventilation ( n  = 14) and major surgery ( n  = 9) and received antifungal drugs as prophylaxis and/or empiric treatment. Seven patients developed C auris candidemia/breakthrough candidemia, nine patients had candiduria with/without candidemia and four patients developed surgical site/respiratory infection. Resistance to fluconazole and amphotericin B was detected in 44 and four isolates, respectively. Twelve C auris isolates from eight patients showed reduced susceptibility to echinocandins. Seven isolates contained hostspot‐1 mutations and three isolates from a candidemia patient contained R1354H mutation in hotspot‐2 of FKS1 . Ten patients died, five were cured, two were lost to follow‐up and treatment details for one patient were not available. Conclusions: Our findings describe development of a novel mutation in FKS1 conferring reduced susceptibility to echinocandins in one patient during treatment and unfavourable clinical outcome for many C auris ‐infected patients.